Monitoring ECVET implementation strategies in Europe in 2013 - (:unkn) unknown (Publications Office of the European Union, 2014)
This fourth annual report on European credit systems for vocational education and training (ECVET) "covers 38 countries/regions and the most important forms of formal VET provision, mainly falling under the responsibility of the national authorities (Ministry of Education, national agencies, national boards of education) involved in the survey. It reviews developments up to September 2013 and may encompass relevant developments dating 2009 or before. The main focus is on what stage ECVET has reached in relation to national qualification systems. It asks what countries/regions have decided to keep ECVET on hold, to test it on qualifications, or have a policy commitment to apply ECVET to qualifications. A cluster analysis provides insights into current developments and key challenges." (Editor, BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2 Europa; Europäisches Leistungspunktesystem; Lernergebnisorientierung; Europa